Design of a Decision Support System for Scholarship Award Recommendations Using the TOPSIS Method (Case Study: MTS Al-Hidayah, Jambi City) - Ramdani Saputra; Jasmir; Dodi Sandra (MASE - Media Applied and Engineering, 2025)
Processing scholarship data at MTS Al-Hidayah Kota Jambi takes a relatively long time in determining who is eligible to receive the scholarship and in recording student data there are often errors in inputting student identities so that a scholarship decision support system is needed using PHP programming languages and MySQL DBMS. The author develops the system using the waterfall method and uses the unified model language system model approach using use case diagrams, activity diagrams, class diagrams and flowchart documents. The results of the system can display student assessment data and the results of the calculation of scholarship awarding with the TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution)